Możliwości zastosowania rachunku kosztów działań w jednostkach wykorzystujących odnawialne zasoby przyrodnicze do produkcji energii - Szczypa, Piotr (Application Possibilities of Activity Based Costing in Entities Using Renewable Natural Sources for Energy Production, 2009)
Activity based costing is an instrument of management accountancy which allows to receive multi-sectioned information about costs. It may be used to decision needs in a range of cost management in entities using renewable natural sources for energy production. This type of costing delivers real data about the costs of energy production, which can be used for calculation needs, profitability evaluation, etc.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 83, s. 178-193